Democratization in the Arab world prospects and lessons from around the globe - Miller, Laurel (Santa Monica RAND, 2012)
Daunting challenges lie ahead for Arab countries where revolutions have upended longstanding authoritarian regimes. This monograph aims to help policymakers understand the challenges ahead, form
"National Defense Research Institute."
Keywords: Democratization--Arab countries